2011
DOI: 10.1007/s12665-011-0947-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of heavy metals in sulfide mine tailings and bottom sediment (Salair, Kemerovo region, Russia)

Abstract: The given work focused on solving the problem of environmental geochemistry related to investigation of element speciation, their mobility, and migration in polluted areas. The purpose was to describe quantitatively migration, distribution, and redistribution of heavy metals by the example of the old tailings (Talmovaya sands) of the Lead Zinc Concentration Plant (Salair, Kemerovo region, Russia) and technogenic bottom sediments of the Malaya Talmovaya river. Contents of elements in the sulfide tailings range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
(13 reference statements)
1
11
0
2
Order By: Relevance
“…The NH4-acetate extractant is used to determine the exchangeable elements at pH 4 to 5, and calcite is also dissolved by this extractant (Dold and Fontboté 2001). The exchangeable and carbonate fractions are separated by using the same extractant (NH4-acetate) at pH 7 and 5, respectively (Bogush and Lazareva 2011). The exchangeable fractions of Fe was negligible in all of the tailings samples while those of Zn and Cu were <0.3…”
Section: Batch Leaching Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH4-acetate extractant is used to determine the exchangeable elements at pH 4 to 5, and calcite is also dissolved by this extractant (Dold and Fontboté 2001). The exchangeable and carbonate fractions are separated by using the same extractant (NH4-acetate) at pH 7 and 5, respectively (Bogush and Lazareva 2011). The exchangeable fractions of Fe was negligible in all of the tailings samples while those of Zn and Cu were <0.3…”
Section: Batch Leaching Experimentsmentioning
confidence: 99%
“…The distribution and chemical species of metals in a tailings dam differ, depending on the ore minerals, tailings properties, deposit time, and local climate (Duanmu et al 2011). Several studies have shown changes in AMD generation rates (Bouzahzah et al 2014;Greenhill 2000;Hakkou et al 2008;Lengke et al 2010;Modabberi et al 2013;Morin and Hutt 1998;Schafer 2000) and the leaching behaviors of contaminants from mine sites over time (Bogush and Lazareva 2011;Lee et al 2005;Wang et al 2017;Zhang et al 2016). However, the factors and processes controlling AMD generation and distribution of potentially toxic elements in tailings dams are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between metals in tailings and the surrounding environment and properties of tailings/soil/water have also been widely explored [17,18]. The chemical speciation of metals is also a good indicator for assessing their potential mobility, availability, and toxicity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used technique has been ICP with different detectors: MS [1,2,[6][7][8], AES [3,9,10], and OES [11]. Moreover, XRF techniques with different modification were also used, as these methods can be applied directly with solid samples [5,[12][13][14][15]. One publication described the INAA method for determining elements in bottom sediment [16], and five used the AAS method [4,14,[17][18][19].…”
mentioning
confidence: 99%
“…Moreover, XRF techniques with different modification were also used, as these methods can be applied directly with solid samples [5,[12][13][14][15]. One publication described the INAA method for determining elements in bottom sediment [16], and five used the AAS method [4,14,[17][18][19]. To our knowledge, there have been only two publications in recent years that have applied electrochemical methods for element determination in bottom sediments [20,21].…”
mentioning
confidence: 99%